Adequação das estratégias aos recursos: o caso de empresas do setor de supermercado - Lima, Danielle Pedretti Morais (2005)
The objective of the present work is to evaluate the relation between strategy and structure, both determined on companies management of supermarket business, taking into consideration two approaches: the strategy based on company^s internai resources through an approach called Competition Based on Resources (RBV) which explains the causes ofcompany^s distinctive performances by utilizing their own tangible and non-tangible resources and their competencies; and different structures used by supermarkets showing that the processes vary according to the dynamics ofeach organization, its structure ofperformance. In the current market, where the changes happen in an unequal rhythm, itis not possible to admit inefficient allocation ofresources bybusiness organizations. The research done was ofa qualitative type, aiming the principal data survey about the supermarkets outline, their organizational structure and strategy. The data survey was done in Belo Horizonte, the capital city ofMinas Gerais. The sample was constituted ofnine big, médium and small sized fírms of supermarket business. The results ofthe field work were useful for bounding the conclusions, on which it was identified: the importance of the strategic dimension onthe decision making process; and the resources adequacy towards the structures heterogeneity. It could be realized that the fírms have been presenting a new way of articulating their resources with the use of new technologies, development of new products, training strategies, partnership formation and focuson the full satisfaction ofclients, outlining differentwaysof coordinating, controlling, communicating and revising information, and thus building their own course. It is important to point out that thestructure becomes the precondition in order to obtain competitive advantages. Finally, it is recommended new researcheson the academic and organizational subjects.